Ma‘āyīr Taqyīm Mu‘allimī al-Lughah al-‘Arabīyah li-Ghayr al-Nāṭiqīna bi-hā - Arif ibn Shaj'an Alashimi (Al-Ma‘rifah, 2018)
This research aims to understand and establish criteria for evaluating the performance of the Arabic teachers for non-native speakers. The standards of learning foreign languages and integrating them into the curriculum and its applications in the field of language education. The researcher also pointed to the most important standards in the field of teaching Arabic to non-native speakers. To achieve the objectives set for this study, the researcher followed the descriptive method based on the development of the data required to answer the questions of the study describing the phenomenon under study and derived and analyzed to reach tangible results. The researcher chose this approach because it is comprehensive and provides the researcher with a lot of information about the phenomenon and its relevance to the subject of study. The researcher concluded from this study the results of the most important of which is to prove the role of the educational assessment of the teacher of the Arabic language for non-native speakers and how to achieve the goals of education effectively and strive to provide him with what helps to reflect his ideas abstraction and transfer it to knowledge and planning and application in the best ways to modify the environment of education and the need for educational renewal The need to evaluate the teacher according to basic and functional standards in the educational process such as ACTFI standards, CEFR standards, TESOL standards, Australia’s AFMLTA. The need for teaching Arabic language curricula for non-native speakers to the development and activation.